APLIKASI PRAKTIS MODEL IDENTIFIKASI AUTOREGRESSIVE MOVING AVERAGE EXOGENOUS (ARMAX) DENGAN METODA KUADRAT TERKECIL REKURSIF - Khuriati RS, Ainie (BERKALA FISIKA, 2011)
AbstractEffect on variations in power heating to air temperature in the mosquito box were modelled. Transfer function for temperature ranges from 34.93 oC to 39.93 C determinedexperimentally. A step function used to excite power control and its effect on the air temperaturemeasured. From these information, the transfer function in the ARX and ARMAX form determinedand compared. An analysis of the computational results has confirmed that the ARMAX model andthe recursive least square method are superior to the ARX model and the Extended Least Square method to model the thermal behaviour in the mosquito box as indicated by the level of fitting and system stabilitytedKeywords: Identification, prediction error method, caged mosquitoes